Auditory Outcomes Following Transmastoid and Middle Cranial Fossa Approaches for Superior Semicircular Canal Dehiscence Repair. Issue 10 (December 2021) - Ellsperman, Susan E.; Telian, Steven A.; Kileny, Paul R.; Welch, Christopher M.
Abstract : Objective: To describe postoperative hearing outcomes following transmastoid (TM) and middle cranial fossa (MCF) approaches for semicircular canal dehiscence (SSCD) repair. Study Design: Retrospective review. Setting: Academic, tertiary referral center. Patients: Adults with SSCD who underwent repair between 2005 and 2019. Interventions: Pure tone audiometry pre- and postoperatively after SSCD repair. Main Outcome Measures: Change in air-bone gap (ABG) at 250 and 500 Hz, pure tone average (PTA), bone conduction (BC), and air conduction (AC) thresholds at 500, 1000, 2000, and 4000 Hz for patients undergoing TM and MCF approaches for SSCD repair. Results: The average change in BC PTA for patients undergoing TM (n = 26) and MCF (n = 24) SSCD repair was not significantly different between the two groups. The first and final postoperative PTAs were recorded an average of 1.7 (range 0.30–3.0) and 29.1 (range 3.5–154) months postoperatively. For patients who underwent MCF repair, the average BC PTAs increased (+) by 2.2 dB HL ( p 0.43) and 0.57 dB HL ( p 0.88) at the first and final audiograms respectively compared to +1.27 dB HL ( p 0.53) and a decrease (−) of 0.57 dB HL ( p 0.63) for the TM group. The average changes in low frequency ABG for patients undergoing MCF repair were −4.7 dB ( p 0.08) and −6.9 dB ( p 0.15) at first and final audiograms respectively compared to −4.9 dB ( p 0.06) and −4.1 dB ( p 0.36) for patients who underwent TM repair. There was a high frequency hearing loss noted at 8000 Hz for the MCF (30.0 dB ± 18.7 preop; 41.7 dB ± 21.7 postop; p 0.01) and TM (32.1 dB ± 23.2 preop; 44.3 dB ± 29.6 postop; p 0.001) groups which persisted on long term follow up. Conclusions: Both TM and MCF approaches to SSCD repair can be performed with long-term preservation of hearing. ABGs were reduced in each treatment group but did not reach significance. A high frequency hearing loss (8000 Hz) may be expected with either approach.